Seated postural neck and trunk reactions to sideways perturbations with or without a cognitive task. Issue 3 (June 2015) - Stenlund, T.C.; Lundström, R.; Lindroos, O.; Häger, C.K.; Burström, L.; Neely, G.; Rehn, B.
Abstract Driving on irregular terrain will expose the driver to sideways mechanical shocks or perturbations that may cause musculoskeletal problems. How a cognitive task, imposed on the driver, affects seated postural reactions during perturbations is unknown. The aim of the present study was to investigate seated postural reactions in the neck and trunk among healthy adults exposed to sideways perturbations with or without a cognitive task. Twenty-three healthy male subjects aged 19–36 years, were seated on a chair mounted on a motion system and randomly exposed to 20 sideways perturbations (at two peak accelerations 5.1 or 13.2 m/s2) in two conditions: counting backwards or not. Kinematics were recorded for upper body segments using inertial measurement units attached to the body and electromyography (EMG) was recorded for four muscles bilaterally in the neck and trunk. Angular displacements (head, neck, trunk and pelvis) in the frontal plane, and EMG amplitude (normalised to maximum voluntary contractions, MVC) were analysed. The cognitive task provoked significantly larger angular displacements of the head, neck and trunk and significantly increased EMG mean amplitudes in the upper neck during deceleration, although 10% of MVC was never exceeded. A cognitive task seems to affect musculoskeletal reactions when exposed to sideways perturbations in a seated position.